2014
DOI: 10.1007/978-3-319-04843-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Notch in Osteosarcoma

Abstract: The Notch pathway has been described as an oncogene in osteosarcoma, but the myriad functions of all the members of this complex signaling pathway, both in malignant cells and nonmalignant components of tumors, make it more difficult to define Notch as simply an oncogene or a tumor suppressor. The cell-autonomous behaviors caused by Notch pathway manipulation may vary between cell lines but can include changes in proliferation, migration, invasiveness, oxidative stress resistance, and expression of markers ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 201 publications
0
34
0
Order By: Relevance
“…Although it is widely recognized that the agent intercalates into DNA and generates free radicals, the precise effect of doxorubicin on cancer cells requires further investigation (28). Dysregulated Notch activity has been reported to contribute to the carcinogenesis of osteosarcoma (22), with Notch1 activity appearing to be crucial for the invasion and metastasis of osteosarcoma (25). Furthermore, inhibition of the Notch signaling pathway suppressed osteosarcoma growth in vitro and in vivo (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is widely recognized that the agent intercalates into DNA and generates free radicals, the precise effect of doxorubicin on cancer cells requires further investigation (28). Dysregulated Notch activity has been reported to contribute to the carcinogenesis of osteosarcoma (22), with Notch1 activity appearing to be crucial for the invasion and metastasis of osteosarcoma (25). Furthermore, inhibition of the Notch signaling pathway suppressed osteosarcoma growth in vitro and in vivo (26).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated Notch activity has been reported in an increasing number of malignancies, such as colon (17,18), pancreatic (19,20) and cervical (21) cancer. Additionally, dysregulated Notch activity has been reported to contribute to the carcinogenesis of osteosarcoma (22)(23)(24)(25)(26). However, the role of Notch in osteosarcoma chemoresistance remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Notch signaling in OS seems to be an outcome of paracrine induction from the tumor's microenvironment, mainly from pericytes and endothelial cells. 67 …”
Section: Notch Pathwaymentioning
confidence: 99%
“…It is reported that Notch activity leads to the development of tumors in osteosarcoma cells [18]. The activity of Notch1 in osteosarcoma cells plays an important role in the process of tumor cell invasion and tissue metastasis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of the activity of Notch genes has been detected in various malignancies like colon [12,13], pancreatic [14,15] and cervical [16] cancer. Furthermore, various studies have demonstrated reduced activity of Notch in osteosarcoma [17,18]. Therefore, the present study was designed to investigate the effect of resveratrol on the activity of the Notch signaling pathway in U2OS osteosarcoma cell lines.…”
Section: Introductionmentioning
confidence: 99%